Política climática paulistana: agenda em contínuo aprimoramento - Back, Adalberto Gregório (Universidade Federal de São Carlos, 2012)
This study aims to understand the process of formation and incorporation of climate agenda in environmental and urban policy areas of São Paulo, including contextualizing and the formulation of the law that established the Climate Change Policy in São Paulo (Law 14,933 of June 5, 2009). To do so, based on theoretical assumptions of agenda-setting, we will hold: a literature review of international literature on the mode of action of ICLEI's CCP campaign, qualitative analysis of interviews with some actors who participated in the formulation of the law; survey of the actions converging local municipality to tackling global climate change, and analysis of organizations and instruments created by law. We found that the climate agenda is being built gradually in urban and environmental policy of the city of São Paulo, since 2003, when the municipality joined the Cities Campaign for Climate Protection of Transnational Network of Local Governments, ICLEI and as a result, produced its first inventory of greenhouse gases emissions (GHGs). With the publication of the inventory in 2005, the City received indications of its priorities regarding GHG mitigation. We identified that between the years 2005 to 2007, the political actions in dealing with an interface to local causes and consequences of climate change were expanded in São Paulo. The implementation of urban and environmental policies with climate agenda provided a political learning that led to the formulation of the law 14,933. The law, in turn, provided an institutional legacy that structure the definition of policy problems, policy formulation and the influence of outside groups for the continued inclusion of the climate agenda in the formulation of policies in the municipality.
Keywords: Ciência política; Políticas públicas; Mudanças climáticas; Formação da agenda climática; Município de São Paulo; Redes transnacionais de governos locais; Global climate change; Agenda-setting; City of Sao Paulo; Transnational networks of local governments; CIENCIAS HUMANAS::CIENCIA POLITICA